A Uhf Near Field RFID Reader Antenna Implemented with Fractal Koch Curve - et. al., ChitraVaradhan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper comprises a fractal Koch curve with tapered slot structure subjected to magnetic field strengthanalysis for Ultra High Frequencies (UHF) RFID near field reader antenna. In the design, Variable distance with opposite direction current principle is used. The center frequency of the proposed antenna operates at 897 MHz with bandwidth of 101 MHZ. (853 to 954 MHz). The obtained bandwidth is sufficient to cover the UHF RFID frequency for, Canada (902-928 MHz), Europe andUSA (865-868 MHz). The near field analysis was verified by keeping different liquids and the antenna performance is calculated. During the measurement, the antenna is kept at a distance of 50 mm in z direction and is observed that the interrogation area of proposed antenna is achieved with 243 mm X 190 mm. The result shows that the antenna exhibits the ability to track chemicals in industries and pharmaceutical applicationsmanagement. It is also observed that the proposed antenna is sufficient to operate as commercial tags for near field magnetic induction communication.